Effect of crop diversification and mulching on termite damage to maize in western Ethiopia. (October 2019) - Demissie, Girma; Mendesil, Esayas; Diro, Debela; Tefera, Tadele
Abstract: Termites are major biotic factors that contribute to crop damage and yield losses to maize ( Zea mays L.) in western Ethiopia. This study evaluated mulching maize stover, intercropping maize with soybean ( Glycine max (L.) Merr.) and desmodium ( Desmodium intortum (Mill.) Urb.), and integration of mulching and intercropping for their effectiveness in reducing damage of Microtermes spp mainly Microtermes vadschaggae Sjostedt and Microtermes adschaggae (Sjosted) to maize. Five termite management treatments and a control (sole maize) were arranged in a randomized complete block design with three replicates on 2 farm sites in 2016 and 7 sites in 2017 cropping seasons in Sibu Sire and Gudeya Billa. Results indicated that application of maize stover as mulch combined with animal manure, maize-soybean intercrops and wood ash, maize-desmodium intercrops, and mulching combined with maize-soybean intercrops consistently reduced termite damage to maize in both cropping seasons. These results were comparable to application of Diazinon 60% EC (standard check). In addition, intercropping maize with desmodium, mulching + intercropping maize with soybean, and Diazinon 60% EC reduced the number of lodged plants per plot compared to control. Maize grain yield in treated plots was significantly higher than maize monocrop control. In order to reduce termite damage and to enhance maize productivity, mulching using maize stover, and intercropping of maize with soybean or desmodium can be used in termite prone areas of western Ethiopia and other countries in Africa with similar agroecologies. Highlights: Termites cause a significant damage to maize and other crops in Ethiopia. There is no effective control method of termites for smallholder farmers. We evaluated different termite management practices in western Ethiopia. Results of field experiments confirm effectiveness of termite management practices in reducing damage to maize plant. Better maize grain yield was obtained as a result of the different termite management practices.